Cyclobotryoxide, a phytotoxic metabolite produced by the plurivorous pathogen Neofusicoccum australe. - Andolfi, Anna; Maddau, Lucia; Cimmino, Alessio; Linaldeddu, Benedetto T.; Franceschini, Antonio; Serra, Salvatorica; Basso, Sara; Melck, Dominique; Evidente, Antonio (Journal of natural products, 2012)
Two isolates of Neofusicoccum australe belonging to ITS haplotypes H4 and H1 and associated with grapevine cordon dieback and branch dieback of Phoenicean juniper, respectively, have been shown to produce in vitro structurally different secondary metabolites. From the strain BOT48 of N. australe (haplotype H4) a new cyclohexenone oxide, namely, cyclobotryoxide, was isolated together with 3-methylcatechol and tyrosol. Cyclobotryoxide was characterized as (1S,5R,6S)-5-hydroxy-3-methoxy-4-methyl-7-oxabicyclo[4.1.0]hept-3-en-2-one by spectroscopic, optical, and chemical methods. The strain BL24 (haplotype H1) produced tyrosol along with botryosphaerone D and (3S,4S)-3,4,8-trihydroxy-6-methoxy-3,4-dihydro-1(2H)-naphthalenone. The metabolites obtained from both strains were tested at four concentrations on leaves of grapevine cv. Cannonau, holm oak, and cork oak by the leaf puncture assay. Cyclobotryoxide proved to be the most phytotoxic compound. Tyrosol and cyclobotryoxide were also tested on detached grapevine leaves at concentrations of 0.25 and 0.5 mg/mL. Only cyclobotryoxide was found to be active in this bioassay.
The following values have no corresponding Zotero field: accession-num: 23046443
Keywords: Ascomycota; Ascomycota: chemistry; Bicyclo Compounds, Heterocyclic; Bicyclo Compounds, Heterocyclic: chemistry; Bicyclo Compounds, Heterocyclic: isolation & purif; Bicyclo Compounds, Heterocyclic: pharmacology; Catechols; Cyclohexanones; Cyclohexanones: chemistry; Cyclohexanones: isolation & purification; Cyclohexanones: pharmacology; Juniperus; Juniperus: microbiology; Molecular Structure; mycotoxins; Mycotoxins: chemistry; Mycotoxins: isolation & purification; Mycotoxins: pharmacology; Nuclear Magnetic Resonance, Biomolecular; Quercus; Quercus: drug effects; Stereoisomerism; Vitis; Vitis: drug effects

Winter photoinhibition in the field involves different processes in four co-occurring Mediterranean tree species - Martínez-Ferri, E; Manrique, E; Valladares, F; Balaguer, L (Tree Physiology, 2004)
Photoinhibition was examined in four co-occurring Mediterranean evergreen tree species during two consecutive winters. In response to low temperatures and saturating light, Juniperus phoenicea L., Pinus halepensis Mill., Quercus coccifera L. and Q. ilex ssp. ballota (Desf.) Samp. exhibited marked chronic photoinhibition, indicated by low predawn maximal photochemical efficiency of photosystem II (PSII) (Fv/Fm). Low Fv/Fm values were correlated with high concentrations of xanthophyll cycle components (VAZ) and with the maintenance of high concentrations of zeaxanthin overnight (DPSpd). In all species, however, chronic photoinhibition was enhanced as the winter progressed in the absence of changes in DPSpd, suggesting cumulative damage toward the end of winter.Photoinhibition differed among species: P. halepensis always displayed significantly higher Fv/Fm values; and Q. coccifera had the lowest Fv/Fm values, showing a high sensitivity to the combination of high light and low temperatures. Differences among species were not fully explained by differences in the xanthophyll pool or its de-epoxidation state. Chronic photoinhibition overlapped with a dynamic photoinhibition as shown by the low values of photochemical efficiency of the open reaction centers of PSII at midday. Winter photoprotective strategies differed among species and may involve photoprotective mechanisms in addition to those associated with xanthophylls. The observed species-specific differences matched results obtained for the same species in summer; however, comparison of the two seasons suggests that the higher VAZ concentration observed in winter has an additional structural photoprotective role.
From Duplicate 2 (Winter photoinhibition in the field involves different processes in four co-occurring Mediterranean tree species - Martínez-Ferri, E; Manrique, E; Valladares, F; Balaguer, L)
Keywords: chlorophyll; Chlorophyll: physiology; Juniperus; Juniperus: physiology; photoprotection; Pinus; Pinus: physiology; Plant Leaves; Plant Leaves: physiology; Quercus; Quercus: physiology; Seasons; Sunlight; Trees; Trees: physiology; xanthophyll cycle